Pendidikan Politik Digital dan Tradisional: Dinamika Peran Pemuda dalam Demokrasi Lokal di Indonesia - Solissa, Friskila; Lestaluhu, Said (Universitas Pattimura, 2024)
This study explores the role of youth in digital and traditional political education within Indonesia’s local democratic context, focusing on first-time voters in Waemulang Village, South Buru Regency. It aims to examine how young community leaders contribute to political awareness through adaptive communication strategies that address both technological developments and local needs. Using a qualitative case study approach, data were collected via in-depth interviews, participatory observation, and document analysis. The findings reveal that youth play a vital role in educating novice voters, acting not only as information disseminators but also as facilitators of political dialogue and engagement. Their active involvement significantly enhances political awareness among young citizens. Challenges remain, including low digital literacy and limited political interest. However, digital platforms and social media offer strategic opportunities for developing inclusive, interactive political education models. The novelty of this study lies in combining digital and traditional methods of political communication by rural youth—an area seldom explored in Indonesian contexts. The study recommends strengthening youth capacity as agents of social change through community-based political education and digital integration to foster participatory democracy at the grassroots. These insights contribute to social sciences and humanities discourse, particularly in understanding localized political engagement.